Luther's Wittenberg world the reformer's family, friends, followers, and foes - Kolb, Robert 1941- (Fortress Press, 2018)
In conversations about the Reformation, the name Martin Luther towers above all others. And rightly so. His work, vision, and writings set Christianity on a course of events that would forever change the way that most believers live and understand their faith. And yet, the Reformation was far more than Martin Luther. Around Luther were hundreds of people - fellow teachers and priests, politicians, artists, printers, and spouses - without whose activity and work the Reformation would have progressed much differently. These women and men make up Luther's Wittenberg world, and there is much to be learned from engaging their work. In this monumental work, Robert Kolb introduces us to those individuals. Engaging and informative essays on the social, political, and economic realities of the sixteenth century frame brief introductions to over two hundred supporting "cast members" whose lives played out around Martin Luther. Comprehensively illustrated, with maps, bibliographies, and other resources, Luther's Wittenberg World is a treasure
Keywords: Luther, Martin -- 1483-1546; Umkreis; Wittenberg; Luther, Martin / 1483-1546 / Adversaries; Luther, Martin / 1483-1546 / Disciples; Luther, Martin / 1483-1546 / Friends and associates; Reformation / Germany / Wittenberg (Saxony-Anhalt); Wittenberg (Saxony-Anhalt, Germany) / History